A Potential Mechanism for Targeting Aggregates With Proteasomes and Disaggregases in Liquid Droplets - Mee Hayes, Emma; Sirvio, Liina; Ye, Yu (Frontiers in Aging Neuroscience, 2022)
Insoluble protein deposits are hallmarks of neurodegenerative disorders and common forms of dementia. The aberrant aggregation of misfolded proteins involves a complex cascade of events that occur over time, from the cellular to the clinical phase of neurodegeneration. Declining neuronal health through increased cell stress and loss of protein homeostasis (proteostasis) functions correlate with the accumulation of aggregates. On the cellular level, increasing evidence supports that misfolded proteins may undergo liquid-liquid phase separation (LLPS), which is emerging as an important process to drive protein aggregation. Studying the reverse process of aggregate disassembly and degradation has only recently gained momentum, following reports of enzymes with distinct aggregate-disassembly activities. In this review, we will discuss how the ubiquitin-proteasome system and disaggregation machineries such as VCP/p97 and HSP70 system may disassemble and/or degrade protein aggregates. In addition to their canonically associated functions, these enzymes appear to share a common feature: reversibly assembling into liquid droplets in an LLPS-driven manner. We review the role of LLPS in enhancing the disassembly of aggregates through locally increasing the concentration of these enzymes and their co-proteins together within droplet structures. We propose that such activity may be achieved through the concerted actions of disaggregase machineries, the ubiquitin-proteasome system and their co-proteins, all of which are condensed within transient aggregate-associated droplets (TAADs), ultimately resulting in aggregate clearance. We further speculate that sustained engagement of these enzymatic activities within TAADs will be detrimental to normal cellular functions, where these activities are required. The possibility of facilitating endogenous disaggregation and degradation activities within TAADs potentially represents a novel target for therapeutic intervention to restore protein homeostasis at the early stages of neurodegeneration.